On cubic semisymmetric bi-Cayley graphs on nonabelian simple groups - Jiangmin Pan; Yingnan Zhang (AIMS Mathematics, 2022)
In this paper, we classify cubic semisymmetric bi-Cayley graphs on nonabelian simple groups, extending a remarkable classification of cubic nonnormal symmetric Cayley graphs on nonabelian simple groups.